Pemahaman Pelaku UMKM terhadap Laporan Keuangan sebagai Dasar Pengajuan Pembiayaan Syariah - Putri Nazli (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to explore the understanding of Micro, Small, and Medium Enterprises (MSMEs) actors regarding financial statements as a basis for applying for Islamic financing. Financial statements play a crucial role in assessing business feasibility, especially in Islamic banking which emphasizes the principles of transparency, justice, and accountability. This research employs a qualitative approach using a descriptive method. Data were collected through in-depth interviews and observations involving MSME actors and Islamic banking practitioners. The results indicate that most MSME actors have limited understanding of financial statements, both in terms of preparation and utilization, which impacts their ability to access Islamic financing. Therefore, collaboration between Islamic banks and educational institutions is needed to improve MSME financial literacy, so they are better prepared and have sufficient understanding to prepare financial reports in accordance with Sharia principles. This is expected to improve access to and the quality of financing received by MSMEs in Indonesia.